Effect of acidic MCM-41 mesoporous silica functionalized with sulfonic acid groups catalyst in conversion of methanol to dimethyl ether. (December 2020) - Viscardi, Rosanna; Barbarossa, Vincenzo; Maggi, Raimondo; Pancrazzi, Francesco
Abstract: The global issue of contamination and power reserves has given dimethyl ether (DME) considerable attention. It is an encouraging and clean green material for the future resulting from its clean combustion properties. In this paper, a novel MCM-41-propyl-SO3 H catalyst was successfully prepared with tethering of the active sulfonic acid groups onto the support via covalent bonds. This material was investigated as catalyst for DME synthesis via methanol dehydration in a fixed bed flow reactor at different experimental settings. TGA, NH3 -TPD, SEM, XRD and BET techniques​ were utilized to characterize the synthesized material. MCM-41 sulfonated catalyst showed great thermal stability, high surface area and significant acid loading. The catalytic tests also demonstrated that the maximum methanol conversion was observed at 350 °C and catalyst contact time of 8 s. In addition, the catalyst showed a total selectivity to DME; light hydrocarbons and higher oxygenated compounds were not formed at temperatures above 300° C.